Oral Health of Kindergarten and Third Grade Children with Special Education Needs in Los Angeles County - Kathy Phipps; Maritza Cabezas (Taylor & Francis Group, 2023)
ABSTRACTBackground Little is known about the oral health of children with a special education need (SEN). The purpose of this report is to compare the prevalence of decay experience and untreated decay among children with and without an SEN to determine if children with an SEN are at increased risk of caries.Methods Kindergarten and third grade children in a representative sample of 72 public elementary schools in Los Angeles County received an oral health screening that collected information on the number of teeth with treated and untreated decay. Child-specific information on race/ethnicity, socioeconomic status, primary language and special education status was obtained from the California Department of Education.Results Data is available for 10,392 children. Overall, 11.0% had an SEN. Third graders (13.6%) and males (15.2%) were more likely than kindergartners (9.6%) and females (7.5%) to have an SEN. Asian Americans (6.3%) and children from households with a primary language other than English or Spanish (5.1%) were the least likely to have an SEN. Children with an SEN had a slightly higher prevalence of decay experience compared to children without an SEN (57.6% versus 54.6%) but the difference was not statistically significant (p > 0.05). There were no statistically significant differences in the prevalence of untreated decay (19.6% versus 19.7%) or the mean number of teeth with decay experience (2.7 versus 2.6).Conclusion In Los Angeles County, kindergarten and third grade children with an SEN, compared to those without an SEN, are not at increased risk of developing dental caries.